PERAN PENDIDIKAN AGAMA ISLAM DAN PANCASILA SEBAGAI FONDASI NILAI KEBANGSAAN DAN MORAL GENERASI MUDA MENUJU INDONESIA EMAS 2045: The Role of Islamic Religious Education and Pancasila as the Foundation of National and Moral Values of the Young Generation Towards a Golden Indonesia 2045 - Mantri, Yaya; Caniago, Fauzi (ABISATYA DINAMIKA ISWARA, 2025)
Islamic Religious Education and Pancasila Education play pivotal roles as the foundation of national values and morality for Indonesian youth in facing the challenges towards Golden Indonesia 2045. This study examines how the integration of these two value systems shapes the character of young generations to be religious, virtuous, and strongly rooted in national identity. Islamic Religious Education emphasizes moral development through divine values and social values, while Pancasila strengthens national consciousness with principles of unity, justice, and democracy. The research employs qualitative methods with library research. Findings reveal that the synergy between these educational systems creates a young generation capable of balancing global progress with local values, resisting radicalism, and actively contributing to national development. The study implies the importance of strengthening the integration of religious and national values in education curricula to prepare a superior and virtuous golden generation for 2045.